1999
DOI: 10.1034/j.1399-3003.1999.14d31.x
|View full text |Cite
|
Sign up to set email alerts
|

Asthma therapy modulates priming-associated blood eosinophil responsiveness in allergic asthmatics

Abstract: Eosinophils play an important role in the pathogenesis of asthma. Several pro-inflammatory responses of eosinophils are primed in vivo in this disease. The aim of the present study was to investigate whether regular antiasthma treatment could modulate priming-sensitive cytotoxic mechanisms of human eosinophils.In a randomized, two-centre, double-blind parallel group study, the effect of 8 weeks of treatment with salmeterol xinafoate 50 mg b.i.d., beclomethasone dipropionate 400 mg b.i.d. or both on pulmonary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Adhesion to surfaces, transendothelial migration, and chemotaxis were found to be enhanced in eosinophils isolated from the blood of patients with allergic asthma. 12,14,27,28 However, cytotoxic responses such as degranulation and activation of the respiratory burst were less sensitive for this in vivo priming process. 28 These findings are consistent with the hypothesis that early priming processes are focused on adhesion processes and prepare eosinophils to leave the peripheral blood to inflammatory loci.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Adhesion to surfaces, transendothelial migration, and chemotaxis were found to be enhanced in eosinophils isolated from the blood of patients with allergic asthma. 12,14,27,28 However, cytotoxic responses such as degranulation and activation of the respiratory burst were less sensitive for this in vivo priming process. 28 These findings are consistent with the hypothesis that early priming processes are focused on adhesion processes and prepare eosinophils to leave the peripheral blood to inflammatory loci.…”
Section: Discussionmentioning
confidence: 96%
“…12,14,27,28 However, cytotoxic responses such as degranulation and activation of the respiratory burst were less sensitive for this in vivo priming process. 28 These findings are consistent with the hypothesis that early priming processes are focused on adhesion processes and prepare eosinophils to leave the peripheral blood to inflammatory loci. Cytotoxic responses are then primed during transition from peripheral blood to the inflammatory loci.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this investigation serum ECP was elevated among workers who developed asthma-like and bronchitic symptoms. Previous studies have shown a good correlation between subjects with asthma symptoms and increased levels of ECP [De Blay et al, 1998;Grutters et al, 1999].…”
Section: Discussionmentioning
confidence: 96%
“…27,30 Systemic inflammatory responses during the LAR have been described in several studies and were associated with an increase of blood eosinophil numbers that likely had a primed phenotype. [30][31][32] In this study the mechanisms involved in the systemic innate immune responses of allergic asthmatic subjects were investigated before and after allergen challenge. The allergen-induced priming of peripheral blood eosinophils and neutrophils was measured in atopic subjects with mild asthma with and without allergen-induced LAR.…”
Section: Abbreviations Usedmentioning
confidence: 99%